Estimated direct costs of non‐small cell lung cancer by stage at diagnosis and disease management phase: A whole‐disease model. Issue 1 (21st November 2020) - Buja, Alessandra; Rivera, Michele; De Polo, Anna; Brino, Eugenio di; Marchetti, Marco; Scioni, Manuela; Pasello, Giulia; Bortolami, Alberto; Rebba, Vincenzo; Schiavon, Marco; Calabrese, Fiorella; Mandoliti, Giovanni; et al.
Abstract : Background: Non‐small cell lung cancer (NSCLC) is the first cause of cancer‐related death among men and the second among women worldwide. It also poses an economic threat to the sustainability of healthcare services. This study estimated the direct costs of care for patients with NSCLC by stage at diagnosis, and management phase of pathway recommended in local and international guidelines. Methods: Based on the most up‐to‐date guidelines, we developed a very detailed "whole‐disease" model listing the probabilities of all potentially necessary diagnostic and therapeutic actions involved in the management of each stage of NSCLC. We assigned a cost to each procedure, and obtained an estimate of the total and average per‐patient costs of each stage of the disease and phase of its management. Results: The mean expected cost of a patient with NSCLC is 21, 328 € (95% C.I. −20 897−22 322). This cost is 16 291 € in stage I, 19530 € in stage II, 21938 € in stage III, 22175 € in stage IV, and 28 711 € for a Pancoast tumor. In the early stages of the disease, the main cost is incurred by surgery, whereas in the more advanced stages radiotherapy, medical therapy, treatment for progressions, and supportive care become variously more important. Conclusions: An estimation of the direct costs of care for NSCLC is fundamental in order to predict the burden of new oncological therapies and treatments on healthcare services, and thus orient the decisions of policy‐makers regarding the allocation of resources. Key points: Significant findings of the study: The high costs of surgery make the early stages of the disease no less expensive than the advanced stages. What this study adds: An estimation of the direct costs of care is fundamental in order to orient the decisions of policy‐makers regarding the allocation of resources. Abstract : The high costs of surgery make the early stages of the disease no less expensive than the advanced stages. An estimation of the direct costs of care is fundamental in order to orient the decisions of policy‐makers regarding the allocation of resources.